“I Wouldn’t Lie to You. Well… That’s a Lie”: an analysis of lies expressed by Rick C-137 in Rick and Morty Season 1 - Lai, Glodie Cheng Yan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Language assumes a significant role in communication and expression, especially in cinematic and television productions. Despite the widespread popularity of the American animated series, Rick and Morty has not been extensively explored within the field of language and linguistics. This paper addresses this gap by examining the linguistic dimension of Rick and Morty, featuring the deceptive discourse of the character Rick C-137 in Season 1. With McCornack’s Information Manipulation Theory (IMT) as the theoretical foundation, this study aims to achieve 2 objectives: (i) investigate the dimensions in which information are manipulated by Rick C-137 in his deceptive messages and (ii) analyse the methods employed by Rick C-137 in his deceptive discourse. To achieve these objectives, qualitative content analysis is utilised on the transcripts of all 11 episodes of Rick and Morty Season 1. The findings of the study discover that Rick C-137 manipulates information along all four dimensions throughout the season: quantity, quality, relation and manner. Furthermore, the analysis unveils two distinct methods of information manipulation employed by Rick C-137: (i) manipulation along a single dimension and (ii) manipulation along two dimensions. While contributing to the knowledge pertaining to linguistic manipulation in Rick and Morty Season 1, these observations also offer valuable insights to the intricate world of deceptive communication within the context of animated series.